Ethics education in the Philippines moving forward : learnings from the pandemic - Caslib, Bernardo N. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Until before the COVID-19 pandemic came, the teaching of ethics as a required course for all undergraduate students in Philippine universities remain oral in tradition. Discussion and interaction, not to mention lectures inside the classroom, remain pivotal in approximating the intended learning outcomes and competencies of the course. With the uncertainty and challenges posed by the COVID-19 pandemic in the past years, especially among developing countries, education as a whole, but ethics education, in particular, faced the enormous task of delivering its promise to its learners. While internet-mediated learning has been the buzzword for many and has been the learning modality since the pandemic started, the question of effectivity remains in ethics education until now, especially in a country dubbed as among the lowest ranked in internet speed and availability. This article examines the Philippine situation and the state’s response to the educational disruption caused by the COVID-19 pandemic. It shall then outline ethics education’s specific challenges that have been noted since the beginning of the pandemic like connectivity, availability of materials, alignment of learning outcomes with methods of delivery and evaluation, and then take up a possible road map with the solutions applied in maneuvering the terrain of an ethics education in the face of a pandemic and beyond. It is recommended that further research be undertaken toward the direction of hybrid instruction in ethics and philosophy and even MOOCs or massive open online courses in ethics.